Pemanfaatan Program Transformasi Perpustakaan Berbasis Inklusi Sosial dalam Mendukung Pertumbuhan Ekonomi yang Inklusif dan Berkelanjutan Sesuai dengan Tujuan Program SDGs Indonesia 2030 - Fandi Rahman Hidayat; Sofia Nur Aisyah; Felisha Ghassani (Media Pustakawan, 2022)
The National Library of Indonesia in its program is Social Inclusion-Based Library Transformation where libraries must be able to improve people's welfare. Library transformation based on social inclusion of libraries has a role to support the UNESCO Sustainable Development Goals Indonesia 2030 program. There are at least 3 objectives of the SDGs program that can be supported by activities carried out by libraries. The aim of the research is to find out the social inclusion-based library transformation, and to find out its role with the SDGs program, especially in the aim of supporting inclusive and sustainable economic growth. The chosen method is phenomenology with a descriptive qualitative approach. The results of this study, the library has utilized the Social Inclusion-Based Library Transformation Program in supporting inclusive and sustainable economic, social and cultural growth in accordance with the 2030 Indonesian SDGs Program Objectives.Â